2014
DOI: 10.1002/dys.1489
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Dyslexia and Phonological Processing in European Portuguese Orthography

Abstract: This study analyzed the performance of phonological processing, the diagnostic accuracy and the influence on reading in children who were native speakers of an orthography of intermediate depth. Portuguese children with developmental dyslexia (DD; N = 24; aged 10 to 12 years), chronological-age-matched controls (CA; N = 24; aged 10 to 12 years) and readinglevel-matched controls (RL; N = 24; aged 7 to 9 years) were tested on measures of phonological processing (phonological awareness, naming speed and verbal sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 79 publications
8
17
0
Order By: Relevance
“…As expected and already found in Portuguese children (e.g. Moura et al, ; Pacheco et al, ; Sucena et al, ) and adults (Lima & Castro, ), college students showed a frequency effect, with significantly more high‐frequency words read in 30 s ( M = 65.90, SD = 7.74; 95% CI [63.70, 68.10]) than low‐frequency words ( M = 58.94, SD = 9.70; 95% CI [56.18, 61.70]), F (1, 49) = 78.50, p < .001, and a lexicality effect, with better performance for high‐frequency and low‐frequency words than for non‐words ( M = 43.70, SD = 8.81; 95% CI [44.80, 49.80]), both F s(1, 49) > 300, p s < .001. Performance in the 1‐min TIL was significantly associated with the three lists of the 3DM test: high‐frequency words, r = .48; low‐frequency words, r = .58; and non‐words, r = .69, all p s < .005, demonstrating, as expected, that the two tests share reading processes (Elbro et al, ; García & Cain, ; Lewandowski et al, ; Nation & Snowling, ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As expected and already found in Portuguese children (e.g. Moura et al, ; Pacheco et al, ; Sucena et al, ) and adults (Lima & Castro, ), college students showed a frequency effect, with significantly more high‐frequency words read in 30 s ( M = 65.90, SD = 7.74; 95% CI [63.70, 68.10]) than low‐frequency words ( M = 58.94, SD = 9.70; 95% CI [56.18, 61.70]), F (1, 49) = 78.50, p < .001, and a lexicality effect, with better performance for high‐frequency and low‐frequency words than for non‐words ( M = 43.70, SD = 8.81; 95% CI [44.80, 49.80]), both F s(1, 49) > 300, p s < .001. Performance in the 1‐min TIL was significantly associated with the three lists of the 3DM test: high‐frequency words, r = .48; low‐frequency words, r = .58; and non‐words, r = .69, all p s < .005, demonstrating, as expected, that the two tests share reading processes (Elbro et al, ; García & Cain, ; Lewandowski et al, ; Nation & Snowling, ).…”
Section: Resultssupporting
confidence: 82%
“…Specifically, the 1‐min TIL scores were significantly associated with phoneme awareness, showing that the association previously reported in Portuguese children, including dyslexics (e.g. Moura et al, ; Sucena et al, ), continues to be reliable in young educated adults. The present results also converge with those showing word length effects (a trademark of phonological decoding at grapheme–phoneme unit‐level) in Portuguese college students, who flexibly adopt a phonological decoding strategy in specific reading conditions (at least in lexical decision and in reading aloud mixed lists of words and non‐words; Lima & Castro, ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…From the above overview of the literature, two issues remain. First, children with dyslexia show both phonological awareness and word reading efficacy deficits (e.g., Moura et al, 2015). They still improve in phonological awareness when they grow older, whereas typically developing children are already at ceiling level in the lower grades of primary school (de Jong & van der Leij, 2003;Dandache et al, 2014).…”
Section: The Present Studymentioning
confidence: 99%
“…Consequently, children with lower phonological skills are more likely to be diagnosed with dyslexia (Boets et al, 2010). Phonological awareness deficits in children with dyslexia have been shown to last into late adolescence (Bekebrede, van der Leij, Plakas, Share, & Morfidi, 2010; Melby‐Lervag et al, 2012; Moura, Moreno, Pereira, & Simões, 2015). However, it has also been found that such deficits in phonological awareness in children with dyslexia may change over time.…”
Section: Introductionmentioning
confidence: 99%